Digital Storytelling For Enjoyable and Effective Learning in the Technological Era (2020–2025): Digital Storytelling Untuk Pembelajaran Yang Menyenangkan Dan Efektif Di Era Teknologi Periode 2020-2025 - Puspitasari, Hayu Ratih; Widiarti, Nuni; Subali, Bambang (Universitas Muhammadiyah Sidoarjo, 2025)
Digital transformation in education has led to the development of more interactive and engaging learning methods. One strategy gaining momentum is digital storytelling, which delivers content through visual and narrative-based technologies. This article qualitatively examines digital storytelling’s role in enhancing learning effectiveness and engagement from 2020 to 2025, based on recent research findings. Through a literature review approach, it explores the use of digital media such as flipbooks, animated videos, and web-based storytelling tools. These media have been shown to improve students’ reading interest, idea articulation, conceptual understanding, critical thinking, and media literacy in elementary education. The findings suggest that combining technology with storytelling creates a more meaningful, multimodal learning experience aligned with the demands of 21st-century education. Theoretically, this approach supports the development of adaptive, contextual digital narrative-based learning. Practically, successful implementation requires improved teacher competence and curriculum adaptation to technological developments. A limitation of this study is the lack of direct empirical evidence from classroom applications, as the analysis relies entirely on secondary data. In conclusion, digital storytelling is a relevant and effective approach for tackling modern educational challenges and should be further developed to enrich learning practices in elementary schools. Highlights: Boosts Skills: Improves reading, thinking, and media literacy. Engaging Format: Uses visuals and stories for richer learning. Needs Support: Requires trained teachers and tech-ready curriculum. Keywords: Digital Storytelling, Interactive Learning Media, Educational Transformation, 21st Century Skills, Educational Technology